Work and Earnings of Low-Skill Women: Do Survey Response and Administrative Records Provide Consistent Information? - Haveman, Robert; Wallace, Geoffrey L. (My University, 2005)
The authors find substantial differences in mean earnings and mean employment rates between survey data and Unemployment Insurance data.